Temporary neonatal atrial pacing through the umbilical venous route: A novel technique - Hiren N Doshi; Seema T Lokare (Wolters Kluwer Medknow Publications, 2011)
Atrial pacing in the neonate is rarely done due to constraints of equipment, technical knowhow, and risk of complications. We describe a novel method of atrial pacing in the new born using equipment readily available in any intensive care unit. Atrial pacing can be achieved using an adult bipolar pacing wire directly introduced through the umbilical venous route. We have used this method in 5 neonates, and achieved atrial capture in 4 patients. Temporary atrial pacing is a therapeutic option in a few neonatal arrhythmias, such as atrial flutter, a few types of re-entrant tachycardias, such as accessory pathway mediated tachycardia and junctional reciprocating tachycardia, and has a limited role in cardiopulmonary resuscitation where sinoatrial node dysfunction is suspected.